Investigations of homicide due to differences in parenting style: Case report - Elisa Danik Kurniawati (Science Midwifery, 2023)
Competition or child fighting is one of life's problems that often occurs within the scope of the family in Indonesia or what is commonly called sibling rivalry. The parenting style applied by parents at home is a factor that can influence a child's tendency to have a sense of wanting to compete with their siblings. The type of parenting that tends to be a factor causing sibling rivalry is authoritarian parenting. The existence of sibling rivalry can trigger more extreme actions such as homicide. However, apart from the influence of authoritarian parenting, gender bias in parenting can also affect the occurrence of homicide due to sibling rivalry. Therefore, the prevention that can be done is by not differentiating the parenting style given to each child.